Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Kinerja Karyawan Pandemi Covid-19 - Saqif Haidarravy; Faidal Faidal (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
In the midst of the covid-19 pandemic, CV. Buana Tengka Garment Bangkalan experienced a decline in employee performance and K3 due to employees doing work activities side by side with work machines and equipment. The purpose of this study is to identify the magnitude of the influence of K3 on employee performance in the midst of the covid-19 pandemic on CV. Buana Tengka Garment Bangkalan. The method used is a survey research method using descriptive and inferential quantitative statistical analysis techniques assisted by SPSS version 22 software. The findings and implications are that work safety affects employee performance which can be seen at the t value (3.106 1.673) with a significance value of t ( 0.003 0.05); Occupational health has an effect on employee performance, which can be seen from the t value (7.861 1.673) with a significance value of t (0.000 0.05); Leader or owner of CV. Buana Tengka Garment Bangkalan is advised to continue to develop K3 through training and socialization so as to improve the performance of employees.